Internalisasi Nilai-Nilai Moderasi Beragama pada Anak Melalui Kompetensi Sosial Guru PAI DI MIS NU 2 Pontianak - Fatimah Nur Wasilah; Abdul Mukti; Nur Hamzah (Edudeena: Journal of Islamic Religious Education)
Abstract: Religious moderation education is crucial for children from the moment they start elementary school to nurture their ability to apply religious moderation principles in their daily lives. The foundation of religious moderation education for children is embedded through within their family and school settings. This study used a qualitative descriptive research methodology. The data was collected through observation and interview techniques, books and journals relevant to the research topic. The results of this study identified the pivotal role of PAI teachers in instilling religious moderation values in MIS NU 2 Pontianak students. For examples through effective guidance and mentorship in religious moderation practices and incorporating religious moderation activities and discussions into PAI lessons.